Electrochemical synthesis of methyl sulfoxides from thiophenols/thiols and dimethyl sulfoxide. Issue 6 (6th March 2018) - Du, Ke-Si; Huang, Jing-Mei
Abstract : A new route for a one-pot synthesis of methyl sulfoxides from thiophenols/thiols and dimethyl sulfoxide using an electrochemical technique was developed. Abstract : A new route for a one-pot synthesis of methyl sulfoxides from thiophenols/thiols and dimethyl sulfoxide using an electrochemical technique was developed. This protocol proceeded smoothly by employing electrons and hydrogen peroxide as clean oxidants, and a wide range of aromatic and aliphatic sulfoxides were synthesized in moderate to good yields.